2012
DOI: 10.1111/j.1476-5381.2012.01985.x
|View full text |Cite
|
Sign up to set email alerts
|

Both α1‐ and β1‐adrenoceptors in the bed nucleus of the stria terminalis are involved in the expression of conditioned contextual fear

Abstract: BACKGROUND AND PURPOSE The bed nucleus of the stria terminalis (BNST) is a limbic structure that is involved in the expression of conditioned contextual fear. Among the numerous neural inputs to the BNST, noradrenergic synaptic terminals are prominent and some evidence suggests an activation of this noradrenergic neurotransmission in the BNST during aversive situations. Here, we have investigated the involvement of the BNST noradrenergic system in the modulation of behavioural and autonomic responses induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 72 publications
1
22
0
1
Order By: Relevance
“…Indeed, results from several studies (Hott et al 2012; Luyten et al 2011; Resstel et al 2008; Sullivan et al 2004) that have used lesion or other inactivation procedures to disrupt BNST function, and a variety of behavioral and autonomic measures to assess fear, indicate that it is involved. Even NBQX was found to disrupt freezing to a shock-associated context in Zimmerman and Maren (2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, results from several studies (Hott et al 2012; Luyten et al 2011; Resstel et al 2008; Sullivan et al 2004) that have used lesion or other inactivation procedures to disrupt BNST function, and a variety of behavioral and autonomic measures to assess fear, indicate that it is involved. Even NBQX was found to disrupt freezing to a shock-associated context in Zimmerman and Maren (2011).…”
Section: Discussionmentioning
confidence: 99%
“…CRF (Lee and Davis 1997), calcitonin gene-related peptide (CGRP) (Sink et al 2011, 2013), and pituitary adenylate cyclase-activating peptide (PACAP) (Hammack et al 2009) each increase startle when infused into the BNST and produce other hyper-arousal/anxiety-like effects as well (e.g., Lee et al 2008; Ciccocioppo et al 2003; Sahuque et al 2006; Hammack et al 2010; Sink et al 2013). Research by Morilak and colleagues (c.f., Morilak et al 2003) has pointed to a possible role for galanin, and still others have identified a role for norepinephrine (Deyama et al 2008, 2009; Fendt et al 2005; Hott et al 2012; Schweimer et al 2005), which is found in the BNST at concentrations higher than almost any other brain area (Brownstein et al 1974; Kilts and Anderson 1986). These particular systems are likely to be only the tip of a very large iceberg, with the unique neurochemical makeup of the BNST and its afferents providing as-of-yet unmined opportunities to target with greater precision the most devastating symptoms of acute- and post-traumatic stress disorder, and possibly other anxiety conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the majority of studies that have implicated the BNST in conditioned fear have done so using long-duration fear stimuli such as shock-or withdrawalassociated contexts (Aston-Jones et al 1999;Resstel et al 2008;Luyten et al 2011Luyten et al , 2012Ali et al 2012;Hott et al 2012). Several such studies have directly compared the effects of BNST manipulations on fear evoked by short-duration cues to fear evoked by longer-duration contextual (Sullivan et al 2004;Zimmerman and Maren 2011) .…”
Section: Discussionmentioning
confidence: 99%
“…When rats are later re-exposed to the context, now referred to as the conditioned stimulus, they exhibit freezing behavior and increased autonomic activity, represented by increased mean arterial pressure (MAP) and heart rate (HR) and decreased cutaneous temperature (CT) (Fabri et al, 2014;Hott et al, 2012). The behavioral and autonomic changes are collectively called conditioned emotional response (Resstel et al, 2006).…”
Section: Introductionmentioning
confidence: 99%